2018
DOI: 10.3991/ijet.v13i09.8000
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model to Enhance Virtual Learning Environments with Current Social Networking Perspective

Abstract: A Virtual Learning Environment (VLE) is an accumulation of incorporated soft-ware components, empowering the administration of web-based learning (online learning, e-learning). The quality of VLE is indispensable for the accomplishment of e-learning goals and responsible to engage students during web based learning. The attributes of existing VLES does not completely meet with the requirements of today’s e-learning. Consequently, decreases students’ interest, participation and engagement with web-based e-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(24 reference statements)
0
10
0
2
Order By: Relevance
“…Characteristics of learning resources are based on efforts to occur responsive to changes in society [54]. The level of learning resources must be able to lead participants to learn towards attractive learning behaviour and solutions to the various problems of life [55]. Types of learning resources must emphasize to meet student learning needs that are varied and relevant to the development of technology and information science.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Characteristics of learning resources are based on efforts to occur responsive to changes in society [54]. The level of learning resources must be able to lead participants to learn towards attractive learning behaviour and solutions to the various problems of life [55]. Types of learning resources must emphasize to meet student learning needs that are varied and relevant to the development of technology and information science.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A partir del análisis documental llevado a cabo, el presente estudio mostró que el uso del software de simulación es de gran ayuda en la educación, presencial y distancia (Basri & Siam, 2018;Bojović et al, 2020;Farid et al, 2018;Laeeq & Memon, 2018;(Romero-Rodriguez et al, 2020). Entre las herramientas de simulación, en el ámbito de la ingeniería electrónica, las más usadas para implementación de circuitos son: Multisim, Proteus y Labview (Asparuhova et al, 2018;Dak et al, 2018;Kavianpour, 2019;Lilyanova, 2019;Marianoga & Palczynska, 2018;Srikanth et al, 2019;Tortoreli et al, 2017); Tanto Multisim como Proteus, permiten el desarrollo de diversas prácticas de laboratorio y analizar los resultados de las mismas.…”
Section: Discussionunclassified
“…El uso de herramientas virtuales de aprendizaje está siendo cada vez más frecuente en los sistemas educativos (Laeeq & Memon, 2018). A través de la integración de las TIC's, se están ampliando los horizontes del aprendizaje electrónico; de tal manera que muchas universidades en el mundo ofrecen cada vez más este modo de aprendizaje en su oferta de estudios (Basri & Siam, 2018;Bojović et al, 2020;Farid et al, 2018).…”
Section: Adecuación Del Software a Los Programas De La Materia Electrónica Digital Del Tecnmunclassified
“…As a result, web-based learning techniques have emerged as learning support tools by taking advantage of technology in the teaching-learning process [8]- [11]. One of these learning tools is digital video which is an instructional media that has become popular because the information is presented in an attractive manner that makes students learn more enthusiastically [12], [13]. Moreover, Merkt et al, [14] demonstrated that learning with videos is comparable or even superior to learning with illustrated textbooks because the learners can match the pace of information to their own cognitive level.…”
Section: Introductionmentioning
confidence: 99%